Dose-response relationship between daily screen time and the risk of low back pain among children and adolescents: a meta-analysis of 57831 participants - Cheng Yue; Guo Wenyao; Ya Xudong; Shao Shuang; Shao Zhuying; Zhu Yizheng; Zhou Linlin; Chen Jinxin; Wang Xingqi; Liu Yujia (Komiyama Printing Co. Ltd, 2023)
Background: The risk of low back pain (LBP) increases steeply during adolescence, and adolescents with LBP are more likely to have low back pain in their adult years. This study aimed to investigate the dose-response relationship between daily screen time and the risk of low back pain among children and adolescents. Methods: PubMed, the Cochrane Library, Embase, and Web of Science were searched to collect relevant studies on daily screen time and the risk of low back pain from the establishment of the database up to December 2022. Two investigators independently screened the literature, extracted data, and evaluated the risk of bias in the included studies. Stata16.0 was used to perform a dose-response meta-analysis and the methodological quality evaluation of the included studies. Results: The results of the meta-analysis showed that there is a positive correlation between daily computer time (OR = 1.32, 1.05-1.60), daily mobile phone time (OR = 1.32, 1.00-1.64), daily TV watching (OR = 1.07, 1.04-1.09) and the risk of low back pain, separately. The dose-response meta-analysis showed that there is a linear relationship between daily computer use and low back pain. The risk of low back pain increased by 8.2% for each 1-hour of daily computer use. Conclusions: Screen time is related to the risk of low back pain, and there is a linear relationship between daily computer use and the risk of low back pain. A number of strategic measures should be taken to prevent adolescents from developing severe low back pain.